Spin–Charge Interconversion in KTaO3 2D Electron Gases. Issue 43 (9th September 2021) - Vicente‐Arche, Luis M.; Bréhin, Julien; Varotto, Sara; Cosset‐Cheneau, Maxen; Mallik, Srijani; Salazar, Raphaël; Noël, Paul; Vaz, Diogo C.; Trier, Felix; Bhattacharya, Suvam; Sander, Anke; Le Fèvre, Patrick; et al.
Abstract: Oxide interfaces exhibit a broad range of physical effects stemming from broken inversion symmetry. In particular, they can display non‐reciprocal phenomena when time reversal symmetry is also broken, e.g., by the application of a magnetic field. Examples include the direct and inverse Edelstein effects (DEE, IEE) that allow the interconversion between spin currents and charge currents. The DEE and IEE have been investigated in interfaces based on the perovskite SrTiO3 (STO), albeit in separate studies focusing on one or the other. The demonstration of these effects remains mostly elusive in other oxide interface systems despite their blossoming in the last decade. Here, the observation of both the DEE and IEE in a new interfacial two‐dimensional electron gas (2DEG) based on the perovskite oxide KTaO3 is reported. 2DEGs are generated by the simple deposition of Al metal onto KTaO3 single crystals, characterized by angle‐resolved photoemission spectroscopy and magnetotransport, and shown to display the DEE through unidirectional magnetoresistance and the IEE by spin‐pumping experiments. Their spin–charge interconversion efficiency is then compared with that of STO‐based interfaces, related to the 2DEG electronic structure, and perspectives are given for the implementation of KTaO3 2DEGs into spin–orbitronic devices is compared. Abstract : 2D electron gases formed by sputtering a thin film of Al onto KTaO3 crystals are used to interconvert charge and spin currents with a high efficiency, thanks to the large Rashba spin–orbit coupling in the electron gas. These results are relevant for the integration of quantum oxide materials into spintronics devices.